2012
DOI: 10.1021/ja303054c
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Intramolecular C–H Amination of 1-Aza-2-azoniaallene Salts

Abstract: We report that 1-aza-2-azoniaallene salts, generated from α-chloroazo compounds by treatment with halophilic Lewis acids, participate in intramolecular C-H amination reactions to provide pyrazoline products in good to excellent yield. This intramolecular amination occurs readily at both benzylic and tertiary aliphatic positions and proceeds at an enantioenriched chiral center without loss of enantiomeric excess. A competition reaction shows that insertion occurs more readily at an electron-rich benzylic positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…For example, although five‐membered rings are readily formed using the HLF reaction, six‐ and seven‐membered rings are more difficult to obtain. Thus, a general, one‐pot, C(sp 3 )N coupling reaction would be highly desirable 3–5…”
Section: Methodsmentioning
confidence: 99%
“…For example, although five‐membered rings are readily formed using the HLF reaction, six‐ and seven‐membered rings are more difficult to obtain. Thus, a general, one‐pot, C(sp 3 )N coupling reaction would be highly desirable 3–5…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] In addition, we have shown that these species, which can be thought of as imino-nitrenium cations, can react in C-H insertion reactions to give pyrazolines through a bonding stepwise but energy concerted amination process (Scheme 1, 4  6). 8,9 Scheme 1. Known reactions of 1-aza-2-azoniaallene salts.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to effect direct, carbon-nitrogen bond formation between an N À H group and a C(sp 3 ) À H group by the formal loss of H 2 would significantly enhance the existing toolbox of synthetic methods to build complex nitrogen-containing molecules. Such a transformation, particularly involving N,N-dialkyl secondary amines, would complement processes such as reductive amination and would obviate the requirement of a preoxidized coupling partner (e.g., a carbonyl group).…”
mentioning
confidence: 99%
“…Thus, a general, one-pot, C(sp 3 )ÀN coupling reaction would be highly desirable. [3][4][5] Despite notable recent advances in oxidative CÀC bond formation between two C(sp 3 ) À H groups, [6,7] the corresponding C(sp 3 ) À N coupling remains underdeveloped. In 2008, during the total synthesis of the Lycopodium alkaloid lyconadin A (3; Scheme 1), [8] we demonstrated the efficient, one-pot, conversion of amine 1 into caged pentacycle 2.…”
mentioning
confidence: 99%